2008
DOI: 10.1002/ppul.20772
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elevated dietary cholesterol on pulmonary surfactant function in adolescent mice

Abstract: It has been established that phospholipids and cholesterol interact in films of pulmonary surfactant (PS). Generally it is thought that phospholipids increase film stability whereas cholesterol increases film fluidity. To study this further, we modified dietary cholesterol in mice which received either standard rodent lacking cholesterol (sd), or high cholesterol (2%) diet (hc) for 1 month. Phospholipid stability was investigated by a capillary surfactometer (CS), which measures airflow resistance and patency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Cholesterol from serum lipoproteins is taken up by the type II cell and incorporated into the surfactant before secretion (15). Furthermore, it has recently been demonstrated that mice fed a high cholesterol diet exhibit an increased level of serum cholesterol and that the surfactant obtained from these mice had increased cholesterol values with impaired biophysical function (24). However, Davidson et al (7) demonstrated that lowering levels of serum cholesterol by inhibiting the release of hepatic lipoproteins did not affect surfactant cholesterol levels, due to the ability of type II cells to synthesize cholesterol.…”
Section: Discussionmentioning
confidence: 97%
“…Cholesterol from serum lipoproteins is taken up by the type II cell and incorporated into the surfactant before secretion (15). Furthermore, it has recently been demonstrated that mice fed a high cholesterol diet exhibit an increased level of serum cholesterol and that the surfactant obtained from these mice had increased cholesterol values with impaired biophysical function (24). However, Davidson et al (7) demonstrated that lowering levels of serum cholesterol by inhibiting the release of hepatic lipoproteins did not affect surfactant cholesterol levels, due to the ability of type II cells to synthesize cholesterol.…”
Section: Discussionmentioning
confidence: 97%
“…High-density lipoprotein cholesterol serves a unique function in normal lung physiology [26][27][28]. Recent studies have revealed important roles for cholesterol regulators on pulmonary immune responses to the lung injury and infection [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was somewhat surprising in light of an earlier study conducted by McCrae and colleagues which examined the surfactant system from adolescent female mice fed a high-cholesterol diet [29]. These mice had a significant increase in both their serum cholesterol levels and the amount of cholesterol in their surfactant without marked changes to their lamellar body content or lipid droplets in the lipofibroblast [29]. Furthermore, assessment of surfactant biophysical function using a capillary surfactometer demonstrated decreased airway patency and reduced surface film activity in hypercholesterolemic mice.…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…It is possible that the lungs respond to such a condition through a compensatory mechanism involving lipid storage in pulmonary lipofibroblasts [29] with potential impact on surfactant only in a more chronic condition. A limitation of our study therefore, was that the onset of their hypercholesterolemia was acute and does not represent the human development of the condition due to chronic ingestion of high-fat and high-cholesterol foods.…”
Section: Discussion/conclusionmentioning
confidence: 99%